The New Regulation 2017/1001 on the EU Trade Mark - Draganov, Jivko (Research Papers, 2018)
The report studies the development of the regulations of the European Union trade mark as unitary right. It includes general overview of the evolution of EU’s secondary legislation. The amendments of the substantive law, such as removal of the requirement for graphical representation of the sign and creation of EU certification trade mark are discussed. Some major procedural changes in the proceedings before the EU Intellectual Property Office are also analyzed.
Keywords: EU trade mark